The rhizome oil of Kaempferia rotunda Val - Sirat, Hasnah Mohd; Jamil, Shajarahtunnur; Siew, Lee Wai (Allured Publishing Corporation, 2005)
The chemical composition of the rhizome oil of Kaempferia rotunda isolated by hydrodistillation was analyzed by capillary GC and GC/MS. The main constituents found in the oil were pentadecane (25.4%), bornyl acetate (24.9%), benzyl benzoate (15.3%) and camphor (12.1%).